Towards sustainable freight transportation in Africa: Complementarity of the fuzzy Delphi and best-worst Methods - Emmanuel Anu Thompson; Philip Kofi Alimo; Ruhaimatu Abudu; Pan Lu (Sustainable Futures)
The focus on sustainable freight transportation (SFT) is crucial for a sustainable future, especially with the African Continental Free Trade Area agreement. However, comprehensive research on the environmental, social, and economic aspects of SFT in Africa is limited. This study integrates the Fuzzy Delphi Method (FDM) and Best-Worst Method (BWM) to evaluate 17 determinants of SFT in Africa, revealing greenhouse gas emissions, noise emissions, and accident risk as the most significant challenges. The findings and recommendations will guide professionals and policymakers to implement proactive measures to address challenges in the freight transportation market for a more sustainable future.